Polygenic risk score and coronary artery disease: A meta-analysis of 979, 286 participant data. (September 2021) - Agbaedeng, Thomas A.; Noubiap, Jean Jacques; Mofo Mato, Edith Pascale; Chew, Derek P.; Figtree, Gemma A.; Said, M. Abdullah; van der Harst, Pim
Abstract: Background and aims: Coronary artery disease (CAD) is a complex disease with a strong genetic basis. While previous studies have combined common single-nucleotide polymorphisms (SNPs) into a polygenic risk score (PRS) to predict CAD risk, this association is poorly characterised. We performed a meta-analysis to estimate the effect of PRS on the risk of CAD. Methods: Online databases were searched for studies reporting PRS and CAD. PRS computation was based on log-odds (PRSLN ), pruning or clumping and thresholding (PRSP/C + T ), Lassosum regression (PRSLassosum ), LDpred (PRSLDpred ), or metaGRS (PRSmetaGRS ). The reported odds ratio (OR), hazard ratio (HR), C-indexes and their corresponding 95% confidence interval (95% CI) were pooled in a random-effects meta-analysis. Results: Forty-nine studies were included (979, 286 individuals). There was a significant association between 1-standard deviation [SD] increment in PRS and adjusted risks of both incident and prevalent CAD (OR [95% CI]: 1.67 [1.57–1.77] for PRSmetaGRS, 1.46 [1.26–1.68] for PRSLDpred ). The risk of incident CAD was highest for PRSP/C + T (HR [95% CI]: 1.49 [1.26–1.78]), PRSmetaGRS (1.37 [1.27–1.47]), and PRSLDpred (1.36 [1.31–1.42]). Analysis of model performance demonstrated that PRS predicted incident CAD with C-index of up to 0.71. Importantly, addition of PRS to clinical risk scores resulted in modest but statistically significant improvements in CAD risk prediction, with 1.5% observed for PRSP/C + T ( p  < 0.001) and 1.6% for PRSLDpred ( p  < 0.001). Conclusions: Polygenic risk score is strongly associated with increased risks of CAD. Future prospective studies should explore the usefulness of polygenic risk scores for identifying individuals at a high risk of developing CAD. Graphical abstract: Image 1 Highlights: We estimated the effect of polygenic risk score (PRS) on coronary artery disease (CAD) in a meta-analysis. PRS significantly and independently predicted excess CAD events. Stringent weighting by LDpred and metaGRS shows the strongest associations with CAD. Incorporation of PRS into clinical models improves CAD risk prediction and reclassification.